Phase separation in polysulfone-modified epoxy mixtures: Relationships between curing conditions, morphology and ultimate behavior - Martinez, I. (1999)
Chemorheology of curing as well as the phase separation behavior of polysulfone (PSU)-modified diaminodiphenylmethane-cureddiglycidylether of bisphenol-A epoxy mixtures have been studied using several techniques. The delay in polymerization for the modifiedmixtures with respect to that of the neat epoxy can be explained by dilution and viscosity effects. The immiscibility of these mixtures hasbeen proved for various PSU contents and as a function of the precuring conditions used as well. The control of the generated morphologiescan be performed only by varying the processing temperature. The thermal and dynamic viscoelastic behavior of the modified matrices hasbeen examined and compared to the parent epoxy matrix. Finally, the mechanical properties, including fracture toughness, have beendiscussed in terms of the morphological behavior for an epoxy matrix modified with various amounts of PSU and for a 15 wt.% PSUcontainingmatrix precured at different temperatures.